Formulation and Evaluation of an Innovative Dual-Action Herbal Mosquito Repellent Perfume - Pooja Magar; Akanksha Khamankar; Sumedh Pradhan; Dr.Pravin Wakte (Asian Journal of Pharmaceutical Research and Development, 2025)
Herbal insect repellents shield users from insects that transmit illnesses and dangerous mosquitoes. Since effective protection frequently necessitates insect repellent with harsh chemicals and disagreeable scents, which deter regular usage, the ongoing danger of mosquito-borne diseases worldwide is troublesome.This work introduces a new approach in insect protection to overcome the tension between consumer demand and public health necessity. We suggest a brand-new, multifunctional personal scent that completely rethinks. By developing a wearable fragrance that not only satisfies the senses but also offers strong protection from mosquitoes, our research pioneers additive method. The composition creates a plant-based, non-toxic substitute for traditional solutions by utilizing the inherent repelling and fragrant qualities of specific essential oils. By designing a product that serves as both an individual aroma and a mosquito repellent, this study presents a fresh, bio-rational strategy for personal protection. We speculate that volatile molecules included in essential oils generated from plants have two inherent qualities: they have a pleasant scent and can interfere with mosquito sensory circuits.